Effects of Social Networking Sites on The Effectiveness of Job Opportunity Acquisition in Labour Markets - Amos Ochayi Onojah; Adenike Aderogba Onojah; Abd-el-latif Adekunle ABD-EL-AZIZ; Simon Ayoola TAIWO (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
The vast majority of grads did not find work via social media. Instead, they turned to social media to find specialized recruiters and individual employer websites, where they explored and applied for positions. Several means are used by graduates to obtain information about available jobs in the labour markets. Relevant among the means include the social networks, career networking sites, friends and family, internship, recruitment agency among others. SNSs are web-based programs that allow individuals and organizations to create, engage with, and share new or existing user-generated or existing material in digital environments via multi-way communication. This study investigated (i) the means by which graduates acquire information about jobs in labour markets; (ii) effect of the social networking sites on job opportunity in Nigeria. The study was a cross sectional study which. The responses from the respondents were coded and analyse to beautify the study in terms of analysis, discussions and conclusions. The findings of the study that majority of the respondents got information about jobs through social networking sites and Social networking sites have positive effect on job opportunities.